2022
DOI: 10.3389/fnbot.2022.837494
|View full text |Cite
|
Sign up to set email alerts
|

A Robot-Assisted Therapy to Increase Muscle Strength in Hemiplegic Gait Rehabilitation

Abstract: This study examines the feasibility of using a robot-assisted therapy methodology based on the Bobath concept to perform exercises applied in conventional therapy for gait rehabilitation in stroke patients. The aim of the therapy is to improve postural control and movement through exercises based on repetitive active-assisted joint mobilization, which is expected to produce strength changes in the lower limbs. As therapy progresses, robotic assistance is gradually reduced and the patient's burden increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…A recent study showed a significant increase of muscle strength in hip abductors and knee flexors on both sides in adult hemiplegic after RAGT (20). Our study showed an overall improvement of strength in all the lower limb muscles.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study showed a significant increase of muscle strength in hip abductors and knee flexors on both sides in adult hemiplegic after RAGT (20). Our study showed an overall improvement of strength in all the lower limb muscles.…”
Section: Discussionsupporting
confidence: 75%
“…Finally, the percentage of change that occurred between with and without electrostimulation variables was calculated. For this purpose, the following equation was applied [ 7 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Hemiparesis stands out as very frequent and widely recognized impairment that had been reported in approximately 65% of patients [ 4 ]. Gait recovery is an important aspect of stroke rehabilitation and a primary goal for most patients [ 5 7 ], because gait is of fundamental importance in the activities of daily living [ 8 ]. Thus, for improvement of poststroke gait impairment, numerous rehabilitative training methods have been developed, such as overground walking, cycling, treadmill walking, balance and cardiorespiratory training, repetitive standing exercise, proprioceptive neuromuscular facilitation, repetitive transcranial magnetic stimulation and electrostimulation [ 9 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation therapies have made great strides in recent years, where information technology, robotics, and the design of exoskeletons have been key elements in new therapies ( Pelier et al., 2021 ). These allow the practitioner to have more information to evaluate the response to certain exercises and then adapt the therapy mechanism or exoskeleton to the biomechanics, requirements, and demands of the patient ( Gil et al., 2022 ). Additionally, it allows the performance of more prolonged and repetitive exercises compared to those offered in traditional rehabilitation therapy ( Mancisidor et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%